PENGARUH PROGRAM TADARUS HARIAN TERHADAP PRESTASI BELAJAR MATA PELAJARAN AL-QUR’AN HADITS SISWA KELAS VII MADRASAH TSANAWIYAH MUHAMMADIYAH 1 GEMOLONG TAHUN PELAJARAN 2022/2023 - Amintoyo, Amintoyo; Mulyanto, Mulyanto; Amin, Lailla Hidayatul (STKIP Pesisir Selatan, 2025)
Islamic education plays a vital role in shaping students’ character, morality, and spirituality through the teaching of the Qur’an and Hadith as the core of Islamic values. One practical implementation at MTs Muhammadiyah 1 Gemolong is the daily tadarus program conducted every morning before the start of classes. This study aims to examine the effect of the daily tadarus program on students’ learning achievement in the Qur’an and Hadith subject for seventh-grade students in the 2022/2023 academic year. The population of this study consists of all 215 students at MTs Muhammadiyah 1 Gemolong, divided into three grade levels (VII, VIII, and IX). The research sample includes 35 students from grade VII, where the daily tadarus program is implemented most intensively as part of the school’s morning spiritual habituation. A quantitative approach with a correlational design was employed. Data were collected using a Likert-scale questionnaire and students’ academic records, and analyzed with SPSS version 25 through validity, reliability, normality, heteroscedasticity, and simple linear regression tests. The findings reveal that the daily tadarus program has a positive and significant effect on students’ learning achievement, with a significance value of 0.002 (<0.05) and a determination coefficient of 0.251. This indicates that tadarus activities contribute 25.1% to the variation in students’ academic performance.